Penokohan Series Alrawabi School for Girls Karya Tima Shomali Tinjauan Intrinsik - Fikriyah Nadia Alkatiri; Ilham Ramadhan; Haeriyyah (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2023)
ABSTRACTCHARACTERIZATION OF ALRAWABI SCHOOL FOR GIRLS SERIES BY TIMA SHOMALI (INTRINSIC REVIEW)Fikriyah Nadia Alkatiri